Foreign trade and human capital - Zook, Paul D.; John E. Owens Memorial Foundation, Dallas (Dallas : Southern Methodist University Press, 1962)
The studies cover: (1) the role and importance of investment in human capital, (2) the U. S. foreign aid program, (3) economic integration, and (4) a comparison of development rates in three developing countries.
"A Jno. E. Owens Memorial Foundation publication."
"Seven studies ... presented as lectures at Southern Methodist University in 1960 and 1961 under the auspices of the Jno. E. Owens Memorial Foundation."
Includes bibliographical references and index.
osa 07/06/2018
Loans
Keywords: Economic assistance, American; Economic policy; Manpower; Developing countries; Latin America